Les savoirs - outils de distinction et de légitimation dans le cadre d’une gestion durable : le cas des pêcheurs à pied d’ormeaux - Frédérique Chlous-Ducharme (VertigO, 2005)
Leisure activities in maritime environment can affect biological varieties. The gathering-up of shellfish (ear-fish) is a widespread practice by the Atlantic Channel seashore ant it is therefore carefully watched by the persons in charge of the different natural areas. The observations and interviews carried out in the nature reserve of the islands “Sept-îles” (Fce) unable us to describe and analyse these social practices. Indeed they can’t solely be considered as noxious gathering-up activities. They also constitute a way to appropriate a cultural knowledge (know-how, behaviour…) and therefore take part in the construction of individual and collective identities. Knowledge and know-how are two basics elements used by the fishermen (who collect ear-fish) in order to make a distinction between a “tourist” and a fisherman. Then, manners and the rules of behaviour are used to separate fishermen with traditional methods from those whose methods have devastating effects. These categorizations unable us to understand the varieties of one practice which cannot be grasped if we used sociological critera (gender, age, address, job). And yet an acute analyse of the differences between the practices and those who practice is necessary to understand what is at stake when managing decision are taken for these areas. In a concerted management the rightful practices claimed by the actors can only derive from these distinctions.